Optimization of Cooking Time of Chicken Meat Loaf Prepared With Oven Cooking - Singh, Sanjay; Pathak, Vikas; Goswami, Meena; Verma, Arun Kumar; V, Rajkumar; Kumari, Renu (Journal of Meat Science, 2022)
The present study was carried out to effect of oven cooking at 180ºC for 15 minutes (OC1), 20 minutes (OC2) and 25 minutes (OC3) on various physico-chemical properties, texture profile analysis, colour parameter, mineral content as well as sensorial properties of chicken meat loaf. There was no significant difference in pH, protein and ash content among the treatments. Cooking yield, moisture content, fat retention, water activity and moisture retention values decreased significantly (P
Keywords: Chicken meat loaf; oven cooking; Texture; mineral content